Indeks Biaya Ekonomi dalam Perhitungan Bantuan Partai Politik Kabupaten Kotabaru - Abdillah, khubbi; Rusmin Nuryadin, M; Irwansyah, Irwansyah (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2025)
Financial assistance strengthens the existence of Political Parties in carrying out their fundamental role in a democratic society as intermediaries between the community and the government. The increase in financial assistance to Political Parties is analyzed based on the analysis of the results of empirical studies on the implementation of Political Education, macro analysis of Kotabaru Regency, analysis of the fiscal capacity of Kotabaru Regency, regional fiscal capacity of Kotabaru Regency, analysis of the formulation of the calculation of the value of financial assistance to Political Parties. Based on the macroeconomic analysis, the recommended value of assistance per vote is IDR 15,000 per vote. With the value of assistance to political parties of IDR 15,000 per vote in the 2024 election with a total of 164,953 valid votes, the amount of budget required in the 2026 Regional Budget is IDR 2,474,295,000. The formulation and calculation of the economic cost index of financial assistance to Political Parties needs to be made in Regional Regulations, so that the performance indicators of Political Parties and financial assistance can be measured annually.